PEMASARAN SELEDRI DI DESA OEPAHA KECAMATAN NEKAMESE KABUPATEN KUPANG - Maria C K Nadjib; Alfetri N.P Lango; Paulus Un (Buletin Ilmiah Impas, 2020)
The research, which was conducted in the village of Oepaha, Nekamese District, Kupang Regency, from June to July 2019, aims to identify marketing channels, capabilities and margins, and the share and benefits of celery marketing for farmers. The location of the research was determined using purposive sampling methods, considering that the location was the most important supplier area for celery in Kupang Regency. The population in this study was the farming community in Oepaha Village, Nekamese district, Kupang Regency,in the amount of 96 celery farmers. The sampling methods is carried out by simple random sampling according to the Slovenian formula, so that a sample of 49 celery farmers is obtained. Sampling for marketing institutions was determined by selecting the marketing institutions which directly involved in celery marketing using snowball sampling methods. In the end, respondents selected marketing institutes consisting of village collectors amounted to 4 people and retailers amounted to 4 people. The analysis of the data used in this study includes descriptive analysis, marketing margin analysis, farmer's share analysis and marketing profit analysis. The results showed that the marketing channel for celery carried out by farmers consisted of two channels, namely farmers directly to consumers and farmers to consumers through intermediaries, namely village collectors and retailers. Celery marketing functions that arise are the functions of sales, purchases, transport, standardization and financing and market information on the zero level channel,while sales, purchasing, transportation, storage, standardization, and financing, as well as market information, run on the second level channel. The marketing margin at zero level is Rp. 51.000,-, while the second level marketing channel is Rp. 17,000 at the collector and Rp. 34,000 at the retailer. The percentage of farmer’s share received by farmers is 25% at zero level and 25% at second level channel. The profit from celery marketing in the zero level marketing channel is Rp. 8.261 (farmers), the second level marketing channel is Rp. 16,688 (farmers), Rp. 15.267 (collectors' traders), Rp. 28,029 (retailers).